From Asian to global financial crisis : an Asian regulator's view of unfettered finance in the 1990s and 2000s - Sheng, Andrew (Cambridge ; New Delhi : Cambridge University Press, 2010)
"This is a unique insider account of the new world of unfettered finance. The author, an Asian regulator, examines how old mindsets, market fundamentalism, loose monetary policy, carry trade, lax supervision, greed, cronyism, and financial engineering caused both the Asian crisis of the late 1990s and the current global crisis of 2008-2009. This book shows how the Japanese zero interest rate policy to fight deflation helped create the carry trade that generated bubbles in Asia whose effects brought Asian economies down. The study's main purpose is to demonstrate that global finance is so interlinked and interactive that our current tools and institutional structure to deal with critical episodes are completely outdated. The book explains how current financial policies and regulation failed to deal with a global bubble and makes recommendations on what must change"--Provided by publisher.
Things fall apart -- Japan and the Asian crisis -- The beam in our eyes -- Banking: the weakest link -- Washington consensus and the IMF -- Thailand: the karma of globalization -- South Korea: strong body, weak heart -- Malaysia: the country that went its own way -- Indonesia: from economic to political crisis -- Hong Kong: unusual times need unusual action -- China: rise of the dragon -- From crisis to integration -- The new world of financial engineering -- What's wrong with financial regulation? -- The global financial meltdown -- A crisis of governance.
Includes bibliographical references (p. 433-463) and index.
Keywords: Finance -- Asia; Financial crises -- Asia